(Invited) Electrical Atomic Force Microscopy for 2D Transition Metal Dichalcogenide Materials. (18th April 2017) - Celano, Umberto; Virkki, Olli; Mascaro, Marco; Mehta, Ankit Nalin; Bender, Hugo; Chiappe, Daniele; Asselberghs, Inge; Paredis, Kristof; Hoflijki, Ilse; Franquet, Alexis; Huyghebaert, Cedric; Radu, Iuliana; et al.
Abstract : As Si-based electronic devices are approaching their projected scaling limits, layered two-dimensional (2D) materials such as transition metal dichalcogenides (TMDs) are extensively studied as potential new channel materials and fundamental building blocks of emerging sensors and devices. In this context, MoS2 and WSe2 to name a few, are now available for deposition using different top down approaches. However, their outstanding properties are often degraded during the fabrication processes required for the device integration. For example, 2D TMDs selective growth, patterning and tuning of the electronics properties still remain elusive. Here, electrical atomic force microscopy (AFM) and beam analysis techniques are used to develop a framework of analysis for 2D materials. The latter is applied to understand the local properties of MoS2 comparing pristine material and structures which are selectively grown and patterned. Different growth techniques are investigated. After modelling the tip-sample contact system, we assess the impact of the plasma-induced damages combining the electrical AFMs and Auger emission spectroscopy. We study the local electrical properties of grain boundaries and their transport in patterned MoS2 structures for field-effect-transistor devices by conductive atomic force microscopy (C-AFM).